A positive feedback loop of SIRT1 and miR17HG promotes the repair of DNA double-stranded breaks. Issue 17 (2nd September 2019) - Xie, Luoyijun; Huang, Ruxiao; Liu, Shuang; Wu, Weijia; Su, Ailing; Li, Runkai; Liu, Xu; Lei, Yiting; Sun, Huidi; Liu, Xinguang; Xu, Shun
ABSTRACT: Long noncoding RNAs (lncRNAs) have emerged as critical regulators for gene expression in multiple levels and thus are involved in various physiological and pathological processes. Sirtuin 1 (SIRT1) has been established to exert key roles in the diverse biological process through deacetylation of substrates, including DNA damage repair. Nevertheless, the regulatory relationship between SIRT1 and lncRNAs, and the effect of lncRNA on SIRT1-mediated functions were still far to be elucidated. We herein uncovered that lncRNA miR17HG was notably down-regulated in SIRT1-deficient cells, and significantly up-regulated after ectopic expression of SIRT1. Subsequently, the results of dual luciferase reporter (DLR) showed that SIRT1 dramatically enhanced the promoter activity of the miR-17-92 cluster. Furthermore, we specifically knocked down the previous demonstrated transcription factor for the miR-17-92 cluster, C-Myc, which was the validated substrate of SIRT1. As expected, miR17HG and miR-17-92 miRNAs were evidently down-regulated after silencing of C-Myc; and silencing of C-Myc significantly reversed the effect of SIRT1 on miR17HG expression, suggesting that SIRT1 endowed cells with elevated miR17HG expression through stabilization of C-Myc. What is more, silencing of miR17HG significantly inhibited the repair of DNA DSBs, while enforced expression of miR17HG promoted DSBs repair. Fascinatingly, overexpression of miR17HG evidently enhanced the deacetylation activity of SIRT1, while silencing of miR17HG conferred diminished deacetylation activity. In addition, the results of RIP unraveled the physical interaction between miR17HG and SIRT1. Taken together, we presented evidences that miR17HG and SIRT1 probably formed a positive feedback loop, which exerted a crucial effect on DSBs repair.